(untitled) (Itinera, 2018)
This issue of Itinera collects a selection of the papers presented by the participants of the International Conference "Aesthetics of Emotions. Arts and Cognitive Science" held in October 2016 at the University of Milan. The focus of the conference, on the link between arts, emotions and cognitive sciences, is richly reflected in the themes addressed by the essays, which attempt to put into interdisciplinary dialogue "classical" perspectives of the history of aesthetics with more contemporary perspectives inspired by experimental sciences, in particular psychology, cognitive sciences and the theory of emotions.